2010
DOI: 10.1185/03007995.2010.518304
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofCYP2D6*4genotype on progression free survival in tamoxifen breast cancer treatment

Abstract: While earlier data on CYP2D6 and tamoxifen excluded women with prior chemotherapy, the present analysis suggests that CYP2D6*4 genotype might be particularly crucial in this group of high-risk patients. Key limitations are restriction to the CYP2D6*4 allele and missing data of comedication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…The relationship between breast cancer and the CYP gene family was recently reported, including CYP1B1 (Economopoulos and Sergentanis, 2010;Ozbek et al, 2010), CYP2J2 (Jiang et al, 2007(Jiang et al, , 2009), CYP2D6 (Stingl et al, 2010;González-Tejera et al, 2010;Thompson et al, 2011), CYP2C8 (Knüpfer et al, 2004;Dixit, et al, 2007;Jernström et al, 2009), CYP2C9 (Ekhart et al, 2008;Jernström et al, 2009) and CYP2C19 (Justenhoven et al, 2009;Ruiter et al, 2010;Goetz and Suman, 2010). Several studies have reported different conclusions for the relationship with CYP2C19.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between breast cancer and the CYP gene family was recently reported, including CYP1B1 (Economopoulos and Sergentanis, 2010;Ozbek et al, 2010), CYP2J2 (Jiang et al, 2007(Jiang et al, , 2009), CYP2D6 (Stingl et al, 2010;González-Tejera et al, 2010;Thompson et al, 2011), CYP2C8 (Knüpfer et al, 2004;Dixit, et al, 2007;Jernström et al, 2009), CYP2C9 (Ekhart et al, 2008;Jernström et al, 2009) and CYP2C19 (Justenhoven et al, 2009;Ruiter et al, 2010;Goetz and Suman, 2010). Several studies have reported different conclusions for the relationship with CYP2C19.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference in recurrence-free survival was found in carriers of the *10 allele in 173 Japanese women with primary hormone receptor-positive breast cancer receiving adjuvant tamoxifen [66]. In an Austrian cohort of women with estrogen-positive BC and a history of previous chemotherapy, there were no differences in the time to progression or progression-free survival between carriers of the CYP2D6*4 and the wildtype allele in the overall study cohort [67]. However, in the subgroup of patients receiving adjuvant chemotherapy, homozygous carriers of the CYP2D6*4 allele had shorter time to progression (1.0 vs 6.3 and 5.0 years in *1/*4 and *1/*1 carriers; Wilcoxon p = 0.104) and significantly lower progression-free survival.…”
Section: The Clinical Relevance Of Cyp2d6 Polymorphism For Tamoxifen mentioning
confidence: 95%
“…Overall, no significant difference in tumour free survival was reported; however, a subgroup analysis of patients treated with concomitant chemotherapy showed that CYP2D6*4 poor metabolizers had a shorter mean time interval to disease progression. However, It has to be reported that information on comedication were not available [18] . The impact of CYP2D6 in the outcome of breast cancer was further studied in a population-based cohort trial of 313 women that were adherent to tamoxifen therapy for at least one year (Table 1).…”
Section: Researchmentioning
confidence: 99%